The Effectiveness of Moringa Plant in Reducing Blood Sugar - Al-Darkazali, Waleed; Muhammad Abdallah, Bassam (Al-Nahrain Journal of Science, 2025)
The purpose of this study was to assess the biological mechanisms underlying the effects of Moringa on blood sugar levels. Because of its many health benefits, moringa is crucial for effectively treating diabetes. The information was gathered by doing a comprehensive analysis of earlier research on the effects of moringa on insulin and blood sugar levels. An analysis of its impact on blood sugar levels was conducted using data from clinical studies. According to the findings, moringa lowers blood sugar, improves insulin sensitivity, enhances insulin levels, and lessens the liver’s synthesis of glucose. The significance of endorsing moringa as a secure natural remedy for diabetics is underscored by our findings, which show it has the potential to be a successful supplemental medication to enhance blood sugar regulation.